2022
DOI: 10.3389/fped.2022.805860
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxia Induced Bronchopulmonary Dysplasia-Like Inflammation via miR34a-TNIP2-IL-1β Pathway

Abstract: Lung injury induced by oxygen is a key contributor to the pathogenesis of preterm infant bronchopulmonary dysplasia (BPD). To date, there are comprehensive therapeutic strategy for this disease, but the underlying mechanism is still in progress. By using lentivirus, we constructed microRNA34a (miR34a)-overexpressing or knockdown A549 cell lines, and exposure to hyperoxia to mimic oxygen induce lung injury. In this study, we investigated 4 proinflammatory cytokines, interleukin-1β (IL-1β), tumor necrosis factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“… 19 It was also demonstrated that serum levels of IL-1β, IL-6, IL-8, IL-33, and TNF-α were significantly increased in the early postnatal period of BPD infants. 3 , 4 , 20 However, the above classic markers are mostly non-specific indicators such as inflammatory factors, making it difficult to distinguish between primary disease and BPD in infants with acute respiratory distress syndrome. 2 Therefore, serum IL-6 and IL-33 21 , 22 as inflammatory cytokines, serum ET-1 and KL-6 23 , 24 as lung injury markers were measured, and compared between BPD and non-BPD infants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 19 It was also demonstrated that serum levels of IL-1β, IL-6, IL-8, IL-33, and TNF-α were significantly increased in the early postnatal period of BPD infants. 3 , 4 , 20 However, the above classic markers are mostly non-specific indicators such as inflammatory factors, making it difficult to distinguish between primary disease and BPD in infants with acute respiratory distress syndrome. 2 Therefore, serum IL-6 and IL-33 21 , 22 as inflammatory cytokines, serum ET-1 and KL-6 23 , 24 as lung injury markers were measured, and compared between BPD and non-BPD infants.…”
Section: Discussionmentioning
confidence: 99%
“… 1 However, the early clinical manifestations of BPD are often non-specific. 2 Though several inflammatory factors (such as IL-1β, IL-6, and IL-8) have been reported to be associated with BPD, 3 , 4 these markers lack tissue and disease specificity. Meanwhile, some clinical prediction models have also been developed, but these models contain too many variables, which limits their usability in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Human alveolar basal epithelial cells (A549, AW-CCH011, Abiowell, China) were cultured in DMEM containing 10% FBS, 100 U/ml penicillin, and 100 μg/ml streptomycin, at 37 °C in 95% air and 5% CO 2 . Cultured A549 cells were subjected to hyperoxia induction and ETS1 overexpression assays [ 22 ]. To conduct the hyperoxia experiments, we used subconfluent cells (at 70% with approximately 350–400 cells/mm 2 ) and placed them in sealed glass chambers filled with a gas mixture of 95% O 2 and 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%